2022
DOI: 10.1128/spectrum.01197-22
|View full text |Cite
|
Sign up to set email alerts
|

Emerging of Multidrug-Resistant Cronobacter sakazakii Isolated from Infant Supplementary Food in China

Abstract: As a foodborne pathogen, Cronobacter can cause serious infections in restricted populations and lead to death or chronic sequelae. Although a number of investigations showed that Cronobacter isolates are susceptible to most antimicrobial agents, MDR Cronobacter isolates, isolated mainly from clinical cases but occasionally from foods, have been reported in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…H-NS, MacA, MarA, MarB, marR, mdfA, MdfA/Cmr, mdtA, MdtABC-TolC, mdtB, mdtH, QacE, and SugE in all isolates. These genes were previously identified in C. sakazakii strains investigated in other studies [45][46][47]. All the isolates had genes encoding resistance to at least one of the antibiotic classes such as Aminoglycoside, Fluoroquinolone, Macrolide, Aminocoumarin, Tetracycline, Microcin, peptide antibiotic, and phosphonic acid (mdtA, mdtB, MdtABC-TolC).…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 76%
“…H-NS, MacA, MarA, MarB, marR, mdfA, MdfA/Cmr, mdtA, MdtABC-TolC, mdtB, mdtH, QacE, and SugE in all isolates. These genes were previously identified in C. sakazakii strains investigated in other studies [45][46][47]. All the isolates had genes encoding resistance to at least one of the antibiotic classes such as Aminoglycoside, Fluoroquinolone, Macrolide, Aminocoumarin, Tetracycline, Microcin, peptide antibiotic, and phosphonic acid (mdtA, mdtB, MdtABC-TolC).…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 76%
“…Recently, the emergence of infections caused by Cronobacter spp. in adults, especially the immunocompromised and elderly, has also been observed [16,17,196,197].…”
Section: Cronobacter Sppmentioning
confidence: 87%
“…However, reports on baby food strains resistant to, e.g., chloramphenicol, ampicillin, amoxicillin, tetracycline and cephalosporins, are more frequent. The spread of antibiotic resistance among foodborne isolates poses an important and controllable public health challenge [17,97,197].…”
Section: Cronobacter Sppmentioning
confidence: 99%
“…that were resistant to fosfomycin; 97.5% (39/40) of strains carried the gene fos , which is responsible for fosfomycin resistance, in this study. A recent study from infant supplement food in China found two C. sakazakii strains showed resistance to ampicillin, tetracycline, sulfamethoxazole–trimethoprim, and chloramphenicol [ 41 ]. Another recent report on powdered infant formula milk in Iran showed that 96% (24/25) of C. sakazakii isolates were multi-drug resistant (to at least three different antibiotic classes), and that eight isolates were resistant to a profile consisting of six different classes of antibiotics [ 17 ].…”
Section: Discussionmentioning
confidence: 99%